2015
DOI: 10.1111/gfl.12144
|View full text |Cite
|
Sign up to set email alerts
|

Phase‐field modeling of epitaxial growth of polycrystalline quartz veins in hydrothermal experiments

Abstract: Mineral precipitation in an open fracture plays a crucial role in the evolution of fracture permeability in rocks, and the microstructural development and precipitation rates are closely linked to fluid composition, the kind of host rock as well as temperature and pressure. In this study, we develop a continuum thermodynamic model to understand polycrystalline growth of quartz aggregates from the rock surface. The adapted multiphase‐field model takes into consideration both the absolute growth rate as a functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(76 citation statements)
references
References 54 publications
3
73
0
Order By: Relevance
“…While the recent numerical works (e.g., Ankit et al 2015a, b;Wendler et al 2016) advocate the potential of the phase-field approach in addressing quartz mineral growth in sandstones, the present study in addition to our previous work (Prajapati et al 2017) serves as a basis for new calcite cementation models for carbonate rocks based on sound thermodynamic principles. The present study complements the works of Bons (2001) and Hilgers et al (2001) (who used front-tracking technique) and adds to them.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…While the recent numerical works (e.g., Ankit et al 2015a, b;Wendler et al 2016) advocate the potential of the phase-field approach in addressing quartz mineral growth in sandstones, the present study in addition to our previous work (Prajapati et al 2017) serves as a basis for new calcite cementation models for carbonate rocks based on sound thermodynamic principles. The present study complements the works of Bons (2001) and Hilgers et al (2001) (who used front-tracking technique) and adds to them.…”
Section: Discussionmentioning
confidence: 86%
“…The model has been previously applied to address the growth of minerals such as potash alum (Ankit et al 2013), quartz (Ankit et al 2013(Ankit et al , 2015aWendler et al 2016), and calcite (Prajapati et al 2017). Therefore, for the sake of completeness, we briefly reiterate the model equations.…”
Section: Multiphase-field Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Such models are enticing because they have the potential to predict textures and morphologies that may be compared directly with data from natural samples and laboratory experiments and because they serve as a more rigorous basis for predicting a wide range of rock properties compared with the model types discussed above. To date, most grain/pore scale simulation studies either have involved imposing a predefined diagenetic state as a means to rigorously simulate the impact of diagenetic alteration on bulk rock properties (Bakke & Øren 1997;Øren & Bakke 2002Øren & Bakke , 2003Øren et al 2007;Jin et al 2012;Mousavi & Bryant 2013;Prodanovic et al 2013;van der Land et al 2013;Hosa & Wood 2017) or consider a subset of the diagenetic processes that affect reservoir quality (Abe & Mair 2005;Lander et al 2008a;Marketos & Bolton 2009;Gale et al 2010;Cheung et al 2013;Ankit et al 2015;Lander & Laubach 2015;Wendler et al 2016). Although the promise of models of this class is enormous, considerable work is needed to develop comprehensive modelling approaches that are capable of making accurate pre-drill predictions.…”
Section: Experimental Simulation Of Diagenesismentioning
confidence: 99%
“…[31,33,34] Wendler et al showed that PFMs were able to reproduceh ydrothermal quartz growth experiments ( Figure 6I). [20] Hence, such models provide new insights into various sealings tructures andc orresponding flow paths.T of ate,P FMs have only been used to simulate pure sealing processes on micro-to millimeter scales.H owever, under reservoir conditions,t here should be an interaction of precipitation and dissolution processes, as shown in core-scale reactive percolation experiments under high pressure-temperature conditions with CO 2 -rich brines. [28] Because reactive transport in fractures dependso na vailable response surfaces,m echanically induced fracture geometries are crucial.…”
Section: Multiscale Fluid Flow In Fracturesmentioning
confidence: 99%